PERAN PEMBELAJARAN MANAJEMEN INFORMASI DALAM MENINGKATKAN KOMPETENSI MAHASISWA PERBANKAN SYARIAH: TINJAUAN DARI PERSPEKTIF PENGAJARAN - Acim Acim; Popong Komariah; Dodi Mulyadi (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2025)
This research aims to explore the role of information management learning in enhancing student competency in the Sharia Banking Study Program at STAI Putra Galuh Ciamis. As the sharia banking industry increasingly demands skills in information management and utilization, information management learning becomes a crucial aspect in equipping students with relevant competencies. This study employs a quantitative approach using a survey method involving students and lecturers at STAI Putra Galuh Ciamis. The results show that information management learning plays a significant role in improving students' skills in data management, information analysis, and the application of technology in accordance with sharia principles. Furthermore, teaching methods that integrate case studies and direct practical application are able to strengthen students' understanding in processing information that supports sharia banking operational activities. The implications of these findings highlight the importance of strengthening the curriculum to include information management to produce competent graduates ready to compete in the sharia finance industry